2022
DOI: 10.21203/rs.3.rs-2023552/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dolutegravir-Associated Resistance Mutations after first-line treatment failure in Brazil

Abstract: Background: Since January 2017, the recommended first-line antiretroviral regimen in Brazil is the fixed-dose combination of tenofovir plus lamivudine, with dolutegravir (TL+D). According to the literature, integrase resistance-associated mutations (INRAMs) are rarely found upon virologic failure to first-line dolutegravir plus two nucleoside reverse transcriptase inhibitors. Methods: HIV Sanger sequences of the pol gene were generated from plasma of patients with confirmed virologic failure to first-line TL+D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…One cross-sectional study from Brazil reported that among 113 previously ART-naïve PLWH with confirmed VF while receiving DTG plus tenofovir disoproxil fumarate (TDF)/3TC, seven (6.2%) individuals had major INSTI DRMs [42] (Supplementary Table 1). However, the size of the population receiving DTG plus TDF/3TC and the total number with VF was not reported in this study.…”
Section: Art-naïve Plwhmentioning
confidence: 99%
See 1 more Smart Citation
“…One cross-sectional study from Brazil reported that among 113 previously ART-naïve PLWH with confirmed VF while receiving DTG plus tenofovir disoproxil fumarate (TDF)/3TC, seven (6.2%) individuals had major INSTI DRMs [42] (Supplementary Table 1). However, the size of the population receiving DTG plus TDF/3TC and the total number with VF was not reported in this study.…”
Section: Art-naïve Plwhmentioning
confidence: 99%
“…Cross-sectional studies in which GRT is performed in persons with confirmed VF on a DTG-containing regimen provide an alternate mechanism for assessing the risk of emergent DTG resistance. We described six such studies including one from Brazil of 113 PLWH with confirmed VF on a first-line regimen of DTG plus two NRTIs [42] and five from Sub-Saharan Africa. The studies from Sub-Saharan Africa included approximately 214 individuals most of whom had prior ART experience before initiating DTG treatment [72][73][74][75][76].…”
Section: Dtg Monotherapymentioning
confidence: 99%
“…The deleterious effect of the mutation tends to differ between subtypes, and has been shown to be higher in subtype C than in subtype B (47,48). Nevertheless, in vivo selection of R263K has been observed in subtypes C, D, CRF02_AG, and B (21,(49)(50)(51)(52)(53). Furthermore, some studies suggest that R263K mutations may protect against further selection of resistance mutations within the integrase region (46,54,55) and in the reverse transcriptase region (48).…”
Section: Treatment Outcomes Following Dolutegravir Based-regimens In Ssamentioning
confidence: 99%